Konsep Ekowisata Sebagai Role Model Pengembangan Kawasan Daya Tarik Wisata (DTW) Pada Pengelolaan Subak Perkotaan Denpasar Dalam Perspektif Hukum Kepariwisataan - Dewa Agung Gede Mahardhika Martha; I B. Gede Agustya Mahaputra; I Made Aditya Mantara Putra (Fakultas Hukum, Universitas Warmadewa, 2024)
Tourism is an essential resource for regions that serve as tourist destinations. Indonesia, rich in culture and tourism, boasts a wide range of tourist sites spread across its provinces. One of Indonesia's premier tourist destinations is Bali, an island known for its unique natural and cultural wealth that attracts visitors from around the world. However, tourism development often conflicts with environmental preservation, such as the lack of attention to subak (traditional irrigation systems) in urban areas. Subak, with its cultural foundations, has the potential to be developed into tourist attractions (DTW). Therefore, the concept of ecotourism is seen as a suitable approach for developing tourism attractions in urban subak areas.This research focuses on the role of ecotourism as a model for developing tourism attractions within urban subak systems and the implications of this model based on tourism law principles in Denpasar. The research employs normative legal methods, using both statutory and conceptual approaches. The expected findings aim to serve as a foundation for formulating policies and strategies to develop ecotourism in Denpasar's urban subak areas. These policies and strategies should be grounded in tourism law principles while addressing aspects that need improvement for effective ecotourism implementation in urban subak areas.